Sosialisasi Bahaya Sampah Plastik di Lingkungan Sekitar PT. Petrokimia Gresik - Mohamad Mirwan; Indah Nur Fauziyyah; Muhammad Fuad Ashfihani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The daily use of plastic among the public can cause plastic waste and there are dangers arising from the use of plastic waste. The lack of understanding about the dangers of plastic waste in society is the goal of the activities carried out in this study. One thing that can be done to overcome this problem is to socialize to the public about plastic waste and its dangers and to manage plastic waste to find alternative solutions in accordance with applicable regulations. In the understanding indicator variable that has been determined, the quantitative method is used by conducting a pre-test and post-test. The results of these activities showed that 26% of respondents did not understand the dangers of plastic waste. After socialization activities, it was found that more than 60% of respondents experienced an understanding of the dangers of plastic waste. From this it can be said that the activities carried out in this study are right on target and in accordance with the researchers' objectives that the community can create a good environment and is able to create a healthier environment and can prevent or be able to avoid pollution and the dangers of waste.